PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS KONSTRUKTIVISME PADA PEMBELAJARAN KIMIA KOMPETENSI DASAR KESETIMBANGAN ION DAN pH LARUTAN GARAM - Andami, Fitri; Erviyenni, Erviyenni; Copriady, Jimmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The objective of this research was to develop the constructivism-based student’s activity sheet in the subject of ionic equilibrium and pH of saline solution. The type of this research was Research and Development (R&D) with the 4-D development model which covers Define, Design, Develop, and Disseminate. Because of the limited time and place, this research was only done until the development step and was followed by the limited trial. This research was conducted in the Faculty of Education and Teachers Training University of Riau. The object of this research was constructivism-based student’s activity sheet. The data analysis technique was descriptive statistical analysis by calculating the percentage of validation’s score. The student’s activity sheet validation of eligibility result by 3 lecturers as the experts was 92.19% which categorize as valid and has already fulfilled the eligibility of contents, language, presentation, and the graphic. The student’s activity sheet validation of eligibility result by 3 teachers as the users was 93.92% with valid categorize, It can be concluded that the student’s activity sheet that already developed can be used in the teaching and learning process. Based on the limited trial that already done to 15 students, the respond showed 92% which in the positive criterion.Keywords: student’s activity sheet, constructivism, ionic equilibrium and pH of saline solution.